THE EFFECTIVENESS OF USING TEAMS GAME TOURNAMENT (TGT) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION AT THE TENTH GRADE OF SMK N 1 KOTA BIMA - Suratman; Riana Herlina; Fitri Ningsi (JURNAL PENDIDIKAN BAHASA, 2017)
The porpose of the study was to find out whether the use of Teams Game Tournament (TGT) model will be effective to improve students’ reading comprehension in learning English at the tenth grade students of SMKN 1 Kota Bima in academic year 2015/2016. The research design was experimental research which involves two groups of students: an experimental group and control group. The two group are given different teaching treatment. There will be a pre-test before treatment is given to the experimental and control group and after the treatment were given the same instrument to the experimental and control group. The population of the research were the tent grade students of SMKN 1 Kota Bima which consist of 63 students , 32 students in the experimental group and 31 student in the control group as the sample. The research instrument were used a test. Based on data analyzed, this research applied two techniques, namely descriptive and inferential analysis. The data shown that in the pre-test result, the mean score of the experimental is 6.88 amd the control group is 6.84. it can be interpreted that the students of both groups posses equal intelligence and the resulf of the post-test, it is found that the improment of the meanc score of the experimenatal group is 0.6 points and the control group is o.16. the significance from both of the groups are higher than 0.05 and the values of probability are higher than 0.05 and the obtained t-score was higher than the critical score on the t-table (2,465>1,9996), the difference was statistically significance. This means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.